The Legal Character of Polish Disciplinary Proceedings for Advocates and Legal Advisers in Light of the Case Law of the Polish Constitutional Tribunal and the European Court of Human Rights - Tymon Markiewicz (Review of European and Comparative Law)
The article presents an analysis of the case law of the Polish Constitutional Court and the European Court of Human Rights regarding the nature of disciplinary proceedings for advocates and legal advisers in Poland. The analysis is based on a comparison of the standards outlined in the case law of both courts, demonstrating that disciplinary proceedings in legal professions in Poland have a repressive character, even though they are not formally criminal proceedings.